AN EXAMINATION OF THE VISUAL CLASSIFICATORY ABILITY OF CHILDREN WHO HAVE BEEN EXPOSED TO ONE OF THE "NEW" ELEMENTARY SCIENCE PROGRAMS. - Allen, Leslie R. (Science Education, 1968)
The article describes a study investigating the visual classificatory ability of children who have been exposed a new elementary science program. The so-called "new" programs in elementary science, suggestively, are primarily aimed at three objectives: observation, description, and classification. The acquisition of these three basic skills and understandings is essential for the learning of science. Classificatory behavior, specifically, are important aspects of the cognitive processes. In the present study, a comparison was made between the classificatory abilities of students who have participated in one of the new elementary science programs with students who have not participated. A total of 190 elementary school children were randomly selected from two school populations in California. Out of these, 95 students were kept in the experimental group and 95 in the control group. The results, however, have revealed no significant difference in mean performance between the experimental and control groups.